2022
DOI: 10.1021/acssuschemeng.1c05643
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Ammonia Employing H2O as the Proton Source Under Room Temperature and Atmospheric Pressure

Abstract: Realizing nitrogen fixation under mild conditions is of great significance to modern industry, agriculture, and society. Several approaches have been attempted to replace the conventional Haber–Bosch process to avoid high temperature and pressure reaction conditions, including photocatalysis, electrochemical catalysis, biomimetic catalysis, and so forth. This work demonstrates a conceptually novel, more cost-effective, and environment-friendly approach to nitrogen fixation by mechanical ball milling of nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Figure 3a and Figure S2 show FT‐IR spectra of the powders after ball milling for 4 and 18 h, respectively. The peaks at 840 and 587 cm −1 are assigned to adsorbed NO 3 − species and Fe−O bond, respectively [16] . The peak at 3445 cm −1 is ascribed to the stretching vibration of N−H (ν N−H ) and/or −OH species [14] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3a and Figure S2 show FT‐IR spectra of the powders after ball milling for 4 and 18 h, respectively. The peaks at 840 and 587 cm −1 are assigned to adsorbed NO 3 − species and Fe−O bond, respectively [16] . The peak at 3445 cm −1 is ascribed to the stretching vibration of N−H (ν N−H ) and/or −OH species [14] .…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 840 and 587 cm À 1 are assigned to adsorbed NO 3 À species and FeÀ O bond, respectively. [16] The peak at 3445 cm À 1 is ascribed to the stretching vibration of NÀ H (ν NÀ H ) and/or À OH species. [14] The absorption peaks located at 1454 and 1640 cm À 1 arise from NH 4…”
Section: Structure and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…He et al recently reported the mechanochemical synthesis of ammonia by milling water with nitrogen gas in a planetary ball mill in the absence of an explicit catalyst with a rate of up to 2.8 mg L −1 h −1 . 43 They revealed that abrasion of the milling vessel and grinding balls formed an iron-containing powder in the suspension, which acted as the active material. The oxidation of metal shavings with water during ball milling to facilitate hydrogenation reactions, primarily of organic compounds, has been used several times before, 44,45 but this was the rst application of this approach to nitrogen hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…3–5 Photocatalytic nitrogen reduction technology can achieve sustainable ammonia synthesis under ambient conditions, and is an environmentally friendly and energy sustainable method for ammonia synthesis. 6–8 At present, ammonia synthesis via phocatalytic nitrogen fixation still has a low conversion efficiency. 9–12…”
Section: Introductionmentioning
confidence: 99%